The Belly of Naples and Displaced Meanings, City-as-Body and City-as-Theatre in Commentaries on the Old Town Risanamento: Deconstructing the Stereotype of the Picturesque - Resta, Giuseppe (Writingplace, 2022)
This article considers the formation of stereotypical images associated with the picturesque of the South, analysing the case of Naples. The text examines selected urban images reported before and after the late-nineteenth-century Risanamento period of dramatic renovations of the old town, with a focus on city-as-body and city-as-theatre tropes. The inevitable departure is Il Ventre di Napoli (1884-1906, The belly of Naples) by Matilde Serao. We will see how Serao tackles all contradictions of a built environment teeming with life. We have then connected excerpts from foreign travellers, again before and after the Risanamento, to the pleasures (or sickness) of flesh and theatricality. These displaced meanings parallel many descriptions by writers that travelled to Naples: Charles Dickens and the pantomime, Jean-Paul Sartre’s delirium of flesh and rotten food, Benjamin and the city-